Identifying Javanese Students' Conceptions on Fluid Pressure with Wright Map Analysis of Rasch - Samsudin, Achmad; Aminudin, Adam Hadiana; Novia, Hera; Suhandi, Andi; Fratiwi, Nuzulira Janeusse; Yusup, Muhamad; Supriyatman, Supriyatman; Masrifah, Masrifah; Adimayuda, Rizal; Prahani, Binar Kurnia; Wibowo, Firmanul Catur; Faizin, Mohammad Noor; Costu, Bayram (Journal of Natural Science and Integration, 2023)
This research aims to identify the conception of Central Javanese students on fluid pressure. The survey was conducted in Central Java involving 515 participants (eight grade students about 14 years old) consisting of 177 males and 338 females. The instrument consists of six questions in a four-tier format about fluid pressure and is distributed via Microsoft Form. The analysis was carried out with Rasch analysis and percentages with six categories of conceptions: CU (Conceptual Understanding); PP (Partial Plus); PM (Partial Minus); NU (No Understanding); MC (Misconception); and NC (No Coding). The Rasch analysis shows the Cronbach alpha is 0.68 (Enough) and the distribution of students' conceptions of fluid pressure forms a normal curve. Meanwhile, bias was not found for gender problems in answering the questions. The percentage of the result are: CU (17%), PP (4%), PM (39%), NU (13%), MC (27%), and NC (0%). This indicates that students' conceptions are still dominated by PM and MC categories. Students in the PM category have good characteristics but lack self-confidence. While the MC category is an unexpected result because students are confident in their answers that are wrong or not in accordance with scientific conceptions. Thus, further action is needed to overcome students' misconceptions.Keywords: Students' Conceptions, Fluid Pressure, Rasch Analysis